Analisis Kelayakan Investasi Berbasis Ekonomi Kreatif Di Kota Parepare - Muhajir Suni; Jumardi Jumardi; Asyraf Mustamin (Al-Azhar Journal of Islamic Economics, 2021)
Micro, Small and Medium Enterprises (UMKM) based on the creative economy are strategies implemented by the government in the current economic wave of the Industrial Revolution 4.0 era which has great potential to become one of the drivers that can create an independent, just and prosperous Indonesia in accordance with the vision of the development of Golden Indonesia 2045. The purpose of this research is to analyze the feasibility of developing investment based on creative economy in Parepare City based on technical and technological aspects, market and marketing aspects, and financial aspects. This type of research is field research (field research), using a qualitative descriptive approach. This research produces descriptive data which analyzes the feasibility of a business based on creative economy as a basis for making investment decisions using appropriate analysis. The feasibility analysis uses analysis of non-financial aspects in the form of analysis of technical and production aspects and market and marketing aspects. While the analytical tools used for the feasibility of the financial aspects use Payback Period (PP) analysis, Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The data used in this study are primary data and secondary data. Primary data obtained from observations and interviews. Secondary data is obtained through documents and related business reports. The results showed that handicraft, fashion/textile, printing/ publishing, and culinary businesses from non-financial aspects (technical and technological aspects and market and marketing aspects) and financial aspects (PP, NPV, IRT, and PI) are said to be feasible to develop, so that it meets the investment eligibility criteria.